Biological characteristics, bioactive compounds, and antioxidant activities of off-season mulberry fruit - Liu, Peigang; Zhu, Yan; Ye, Jingjing; Lin, Tianbao; Lv, Zhiqiang; Xu, Zilong; Xu, Lushan; Chen, Leyang; Wei, Jia (Frontiers in Plant Science, 2022)
To understand the yield and quality of off-season mulberry fruits, which are cultivated in open fields from autumn, the biological characteristics, bioactive compounds, and antioxidant activities of them were analyzed. Compared with mulberry fruits in normal season, the fruit length，fruit diameter, single fruit weight, fruit yield per meter strip, and the fruits yield per 667 m2 are significantly lower. The moisture content and juice yield of off-season mulberry fruits are lower than the mulberry fruits in normal season; the pH and soluble solids are higher. The contents of mass fraction of crude protein, total sugar, reducing sugar, total acids, total anthocyanins, and total flavonoids decreased significantly in all batches of off-season mulberry fruits compared with those of normal season. Of off-season mulberry fruits, the contents of glucose, fructose and sucrose, expression, anthocyanin biosynthesis genes, and antioxidant capacity are significantly lower than those in normal season.